(untitled) (Configurazioni. Research on contemporary poetry, 2023)
This text introduces the anthology Nulla che non possano i versi – Antologia de poesia italiana entre o Brasil e a Itália (2018), in which are presented poets, both men and women, born/and, living or currently residing in Brazil, who between the 18th and 21st centuries have adopted Italian as the language of poetry. Each in his or her own way, they are committed to the enhancement of the Italian language and the possibility of establishing fruitful dialogues between Italy and Brazil. One glimpses, in the totality of their work, a possible tradition of writing in the Italian language in Brazil.